The Effect of Hyaluronate-Carboxymethyl Cellulose on Bone Graft Substitute Healing in a Rat Spinal Fusion Model - Lee, Jung Hee; Jeong, Bi O (Journal of Korean Neurosurgical Society, 2011)
The aim of this study was to evaluate the impact of sodium hyaluronate-sodium carboxymethyl cellulose (HA-CMC), an anti-adhesive material for spinal surgery, on bone fusion by applying it to rat spinal models after lumbar posterolateral fusion. Lumbar posterolateral fusion was performed at L4-5 using bone graft substitutes in 30 rats. HA-CMC was injected in 15 rats at a dose of 0.2 cc (HA-CMC group) and a saline solution of 0.2 cc in the other 15 rats (control group). Simple radiographs were taken until postoperative 9 weeks with an interval of one week. At postoperative 4 and 9 weeks, three dimensional computed tomography (3D CT) scanning was performed to observe the process of bone fusion. At 9 weeks, bone fusion was confirmed by gross examination and manual palpation. There were no statistically significant differences in bone fusion between the two groups. 3D CT scanning did not reveal significant differences between the groups. The gross examination and manual palpation after autopsy performed at 9 weeks confirmed bone union in 93.3% of both groups. The anti-adhesive material used for spinal surgery did not have adverse effects on spinal fusion in rats.